Pornography within the mass-media. With reference to a recent document of the Catholic teaching - Fucek, Ivan (Medicina e Morale, 1990)
The author deals with the problem of pornography and violence within the mass-media, with particular reference to a recent document of the Pontificai Council for Social Communications of the Catholic Church. Many paradigmatic elements emerge from this study, which has been carefully carried out using an inductive method, and they have been organized into three main points: 1. Towards an ethical model (an insight into the problem within the vast historical context, in today's conflicting mentality and in the alarm signal expressed by the document): 2. Inappropriate or indirectly refused ethical models (optimal functionality, tolerance and law, conformism and satisfaction, foregoing or autolimitation): 3. Advisable ethical models which underline the importance of the principle of the dialogue and of two criteria, personal wellbeing and common wellbeing.